Perbedaan proporsi stunting pada anak usia 12-24 bulan berdasarkan pemanfaatan pelayanan posyandu di Kabupaten Jayapura, Papua - Yulia Nuradha Kartosiana Wasaraka; Endy Paryanto Prawirohartono; Yati Soenarto (Minat S2 Gizi dan Kesehatan, Prodi S2 IKM, FK-KMK UGM, 2015)
Background: Stunting according to World Health Organization’s standard is a linear growth failure identified by the Z-score value of proportioned height by age (Body Height/Age) that less than -2 of standard deviation. Indonesia has the fifth largest number of stunted children in the world right after India, Nigeria, Pakistan and China. Posyandu service utilization is one of stunting determinants. A number of visits and the activity of infants in using Posyandu services will help the observation of children’s health and nutrition status. Through thoroughly observation chronically malnourished and stunting could be earlier identified, thus the growth failure could be prevented.Objective: to identify the stunting proportion difference of 12-24 months children according to Posyandu services use.Method: Study was conducted by using an observational method and cross-sectional research design. Subjects of study are 12-24 month children in Jayapura Regency. Cluster random sampling method was used to identify 313 children as samples. Observation data was analyzed by using chi-square test and fisher exact test due to a not normally distributed population.Results: There are 19.8% samples identified as stunted children. Chi-square test and fisher exact test showed that there is no significant difference in stunting proportion according to Posyandu service utilization (p>0.05). Meanwhile, there is a significant difference between a number of stunting and number of ISPA (p=0.017) and mothers nutrition knowledge (p=0.025).Conclusion: There is not any difference in stunting number proportion according to Posyandu services utilization.